2004
DOI: 10.1002/jcc.20162
|View full text |Cite
|
Sign up to set email alerts
|

A free energy calculation study of the effect of H→F substitution on binding affinity in ligand–antibody interactions

Abstract: Changes in binding affinity to catalytic antibody 6D9 of chloramphenicol phosphonate derivatives (CPDs) containing H or F were investigated by performing free energy calculations based on molecular dynamics simulations. We calculated the binding free energy, enthalpy, and entropy changes (DeltaDeltaG, DeltaDeltaH, and -TDeltaDeltaS) attributable to H-->F substitution by comparing results for CPDs containing a trifluoroacetylamino group (CPD-F) or an acetylamino group (CPD-H). The calculated DeltaDeltaG, DeltaD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2008
2008
2009
2009

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 35 publications
0
8
1
Order By: Relevance
“…The free energy calculations based on MD simulations were performed according to the same procedures as our previous simulation study of 6D9 by replacing 6D9 with 7C8 and the derivative of CP with CP (Saito et al, 2005). The initial structure of the associated state was prepared as follows.…”
Section: Free Energy Calculations Based On MD Simulationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The free energy calculations based on MD simulations were performed according to the same procedures as our previous simulation study of 6D9 by replacing 6D9 with 7C8 and the derivative of CP with CP (Saito et al, 2005). The initial structure of the associated state was prepared as follows.…”
Section: Free Energy Calculations Based On MD Simulationsmentioning
confidence: 99%
“…One of the authors (MS) and a coworker showed that these simplifications caused serious calculation errors in the free energy values, although only a few atoms in the whole system consisting of tens of thousands of atoms were perturbed. Furthermore, they demonstrated that the free energy perturbation calculations based on MD simulations with long-range coulombic interactions and with all degrees of freedom remarkably decreased calculation errors and gave reliable free energy difference values (Saito and Tanimura, 1995;Horii et al, 2001;Saito, 2002;Saito and Sarai, 2003;Saito et al, 2005). On the other hand, there is no straightforward approach to precisely calculate the absolute binding free energy or the relative binding enthalpy and entropy of large systems such as a protein in water (Rodinger and Pomè s, 2005).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…It is surprisingly difficult to assess the current state of the art in protein-ligand free-energy calculations. Unquestionably, a number of impressively accurate results have been published for both relative and more recently absolute binding free-energy calculations (6)(7)(8)(9)(10)(11)(12)(13)(14), with a general trend toward increased ambition and accuracy as computer power and theoretical understanding have increased. However, it is equally true that binding affinity calculations by simulation methods are not widely used in the pharmaceutical industry (3) and have not yet had the same impact that simpler docking and scoring methods and general molecular modeling have had.…”
Section: Text Protocol Of Simulation Of Mutations Resulting In Strucmentioning
confidence: 99%